John Cage's Cartridge Music (1960): 'A Galaxy Reconfigured'. - Bernstein, David W. (Contemporary Music Review)
Cartridge Music (1960) initiated crucial developments in John Cage's compositional processes and aesthetics. By allowing performers to use different sound sources and texts, it anticipated Cage's more open indeterminate works. By creating a theatrical situation in which performers produce live electronic music, manipulating dials on amplifiers and inserting and removing objects in and out of phonograph cartridges, it looked forward to subsequent works focusing upon actions as well as sounds. Examining the performance practice Cage and his colleagues developed for this work also draws attention to his changing views regarding improvisation. Finally, with Cartridge Music, Cage adapted his music to his evolving perceptions of broader cultural practices. The amplification of sounds that would otherwise be inaudible, constituted a musical metaphor for Cage's rapidly developing 'McLuhanesque' world view in which electronic circuitry creates an extension of the human nervous system to the outside world.